Rapid depolymerization of PET by employing an integrated melt-treatment and diols. (16th January 2023) - Aayanifard, Zahra; Khan, Ajmir; Naveed, Muhammad; Schager, Jessie; Rabnawaz, Muhammad
Abstract: Chemical recycling of poly (ethylene terephthalate) is a long-lasting challenge in the realm of plastic recycling and circularity. Glycolysis of poly (ethylene terephthalate) to its parent monomer, bis(2-hydroxyethyl) terephthalate, is a popular method that can be facilitated with a variety of catalysts, especially zinc-containing catalysts. Herein, we report the effect of using a catalyst and diols during the melt-treatment of poly (ethylene terephthalate) and subsequent glycolysis. Primarily, it has been found that pretreatment effectively eliminates the crystallinity barriers that hinder depolymerization. Additionally, the presence of the catalyst and additive during pretreatment reduced the chain length of the polymer, while creating active sites that accelerate the rate of depolymerization within the structure of the polymer. Depolymerized products were analyzed using in-line FTIR spectroscopy to monitor the reaction along with 1 H NMR and liquid chromatography-mass spectrometry to quantify the compounds in the crude product. Results suggest that the addition of zinc 2-ethyl hexanoate as the internal catalyst and cyclohexanedimethanol as the additive diol during pretreatment shortened the depolymerization time from ∼7 h to only 9 min at 180 °C, thus providing a monomer yield of ∼85.4% Graphical abstract: Image 1 Highlights: Use of catalyst and diols during melt-extrusion of post-consumer PET significantly accelerate the depolymerization process. The presence of catalysts and diols promotes chain scission. Pretreated PET samples in the presence of diols have a low degree of crystallinity (<5%), as compared to the untreated PET >28% crystallinity.